The effect of long-term confinement and the efficacy of exercise countermeasures on muscle strength during a simulated mission to Mars: data from the Mars500 study - Christopher J. Gaffney; Elena Fomina; Dennis Babich; Vladimir Kitov; Konstantin Uskov; David A. Green (SpringerOpen, 2017)
Abstract Background Isolation and long duration spaceflight are associated with musculoskeletal deconditioning. Mars500 was a unique, high-fidelity analogue of the psychological challenges of a 520-day manned mission to Mars. We aimed to explore the effect of musculoskeletal deconditioning on three outcome measures: (1) if lower limb muscle strength was reduced during the 520-day isolation; (2) if type I or II muscle fibres were differentially affected; and (3) whether any 70-day exercise interventions prevented any isolation-induced loss of strength. Methods Six healthy male subjects (mean ± SEM) (34 ± 3 years; 1.76 ± 0.02 metres; 83.7 ± 4.8 kg) provided written, informed consent to participate. The subjects' maximal voluntary contraction (MVC) was assessed isometrically in the calf (predominantly type I fibres), and maximal voluntary isokinetic force (MVIF) was assessed in the quadriceps/hamstrings (predominantly type II fibres) at 0.2 and 0.4 ms−1 using the Multifunctional Dynamometer for Space (MDS) at 35-day intervals throughout Mars500. Exercise interventions were completed 3-7 days/week throughout the 520-day isolation in a counterbalanced design excluding 142-177 days (rest period) and 251-284 days (simulated Mars landing). Exercise interventions included motorized treadmill running, non-motorized treadmill running, cycle ergometry, elastomer-based resistance exercise, whole-body vibration (WBV), and resistance exercise using MDS. Results Calf MVC did not reduce across the 520-day isolation and MDS increased strength by 18% compared to before that of 70-day exercise intervention. In contrast, there was a significant bilateral loss of MVIF across the 520 days at both 0.2 ms−1 (R 2 = 0.53; P = 0.001) and 0.4 ms−1 (0.4 ms−1; R 2 = 0.42; P = 0.007). WBV (+ 3.7 and 8.8%) and MDS (+ 4.9 and 5.2%) afforded the best protection against isolation-induced loss of MVIF, although MDS was the only intervention to prevent bilateral loss of calf MVC and leg MVIF at 0.2 and 0.4 ms−1. Conclusions Mars500 induced significant loss of quadriceps/hamstrings MVIF but not calf MVC. Collectively, these data suggest that muscles with predominantly type I fibres were affected less by isolation compared to type II dominant muscles. MDS and WBV afforded the best protection against isolation-induced loss of strength and thus may have virtue in exploration class missions.